Organ Transplantation for Cystic Fibrosis - Morrell, Matthew R.; Kiel, Sarah C.; Pilewski, Joseph M. (Seminars in Respiratory and Critical Care Medicine, 2019)
Cystic fibrosis (CF) remains the most common indication for lung transplantation in children and the third most common in adults and has the highest median survival posttransplant for all pretransplant diagnoses. Criteria for transplant in patients with CF vary widely among transplant centers and early referral to multiple centers may be needed to maximize opportunities for lung transplantation. Comorbidities unique to CF such as resistant and atypical pathogens like Burkholderia and Mycobacterium abscessus, and cirrhosis require special consideration for lung transplantation but should not be considered as absolute contraindications. For those patients who are listed for lung transplantation, mechanical support with extracorporeal membrane oxygenation and mechanical ventilation can be efficacious as bridges to lung transplantation in experienced centers with adequate resources. Liver and pancreas transplantations are also acceptable options for end-organ disease related to CF and can provide improvements in both quantity and quality of life.
Keywords: cystic fibrosis; lung transplantation; Burkholderia; extracorporeal membrane oxygenation; multiorgan transplantation; nontuberculous mycobacteria